2022
DOI: 10.2196/32982
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Therapeutic Intervention Delivering Biofeedback for Panic Attacks (PanicMechanic): Feasibility and Usability Study

Abstract: Background Panic attacks (PAs) are an impairing mental health problem that affects >11% of adults every year. PAs are episodic, and it is difficult to predict when or where they may occur; thus, they are challenging to study and treat. Objective The aim of this study is to present PanicMechanic, a novel mobile health app that captures heart rate–based data and delivers biofeedback during PAs. Methods In o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…For instance, in our previous paper, health was listed as a trigger of panic attacks by 38% of respondents during the beginning of the 2020 pandemic lockdown in the United States [4]. Other studies have shown an increase of anxiety due to an increase of mortality-related thoughts due to the pandemic [15].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…For instance, in our previous paper, health was listed as a trigger of panic attacks by 38% of respondents during the beginning of the 2020 pandemic lockdown in the United States [4]. Other studies have shown an increase of anxiety due to an increase of mortality-related thoughts due to the pandemic [15].…”
Section: Introductionmentioning
confidence: 90%
“…The daily survey (5 minutes) included items on whether they had experienced a panic attack and associated descriptive information including what they believed their trigger was (open text response), their mood, sleep quality, eating habits (each on a scale of 1-poor, 2-fine, 3-neutral, 4-good, 5-great), stress (on a scale of 1-low stress to 5-very high stress), conflict (yes or no), exercise minutes (open numeric response), and substance use inquiring separately about caffeine, alcohol, prescription drugs, recreational drugs (yes or no) (see Supplemental Table 1 for more detail). Participants were also asked to upload their Apple Watch data weekly after wearing it every day and to use an app, PanicMechanic TM to record their heart rates during any panic attack they experienced [4,22,23]. Only data from surveys are included in subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While individuals with episodic conditions may be able to report their symptoms and even seek help during the episode, an accurate characterization of these symptoms is often difficult, and treatment is often necessary immediately or better prescribed as a preventative measure. For instance, conditions such as experiencing panic attacks [27,28], mania [29,30], suicidality [31,32], epileptic seizures [33], or atrial fibrillation [11,34] would all benefit from objective characterization of frequency, severity, and duration to inform appropriate care. Moreover, while these conditions may feel unpredictable, emerging data suggests digital markers may indicate elevated risk for an episode.…”
Section: Areas Of Opportunity For Digital Medicinementioning
confidence: 99%